Pengaruh Komitmen Organisasi dan Kualias Kehidupan Kerja Terhadap Kepuasan Kerja serta Dampaknya terhadap Kinerja pada Dinas Kesehatan Kabupaten Tanjung Jabung Barat - Kristian Kristian; Fakhrul Rozi Yamali; Ali Akbar; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2023)
Thesis Title The Influence of Organizational Commitment and Quality of Work Life on Job Satisfaction and Its Impact on the Performance of Health Office Employees of Tanjung Jabung Barat. Organizational commitment (X1), quality of work life (X2), job satisfaction (Y) and employee performance (Z) at the West Tanjung Jabung District Health Office, where organizational commitment is in the very good category, quality of work life is in the good category, satisfaction work and employee performance are in the high category. Organizational commitment has a significant effect on job satisfaction. Therefore, it can be concluded that organizational commitment (X1) partially has a significant influence on job satisfaction (Y). The quality of work life has a significant effect on job satisfaction. Therefore, it can be concluded that the quality of work life (X2) partially has a significant influence on job satisfaction (Z). Organizational commitment and quality of work life together influence job satisfaction. Therefore, it can be concluded that the results of testing organizational commitment and quality of work life simultaneously have a significant influence on job satisfaction. Organizational commitment has a significant effect on performance. Therefore, it can be concluded that organizational commitment (X1) partially has a significant influence on performance (Z). The quality of work life influences performance. Therefore, it can be concluded that the quality of work life (X2) partially has a significant effect on performance (Z). Organizational commitment and quality of work life together have a significant effect on performance. Therefore, it can be concluded that the test results are significant, which means organizational commitment and quality of work life simultaneously have a significant effect on performance. Job satisfaction has a significant effect on performance. Therefore, it can be concluded that job satisfaction (Y) partially has a significant effect on performance (Z).